Inoculação micorrízica: consequências no metabolismo e interferência na produção e qualidade de frutos de morangueiro no cultivo sem solo no Brasil e na Espanha - Cecatto, Ana Paula (2014)
The soilless cultivation and in a protected environment to strawberry plant allows lower application of fungicides and insecticides, it allows productivity and quality to fruits, mainly by a bigger number of plants and by the protection given by the environment. Arbuscular mycorrhizal fungi use is an auxiliary technology that provides a better nutrient absorption and stimulates the plant defense system. It also stimulates a bigger synthesis of phenolic composite. Using mycorrhiza in a soilless cultivation and in a protected environment, production costs decrease and the cultivation system is better sustainable and committed to the environment. Chapter I is from Passo Fundo University experiments. Chapter II is from Huelva University experiments in Spain. Experiments in Brazil